Peningkatan Kompetensi Guru dalam Mengembangkan Media Pembelajaran Matematika Berbasis AR/VR Menggunakan WebAR Melalui Pendekatan Techno-Ethno-RME - Farida Nursyahidah; Arif Wibisono; Maya Rini Rubowo (Perkumpulan Kualitama Edukatika Indonesia, 2026)
The development of digital technology is driving the transformation of mathematics learning towards a more interactive, contextual, and learner-centered approach. However, teacher competency in developing immersive technology-based learning media, such as Augmented Reality (AR) and Virtual Reality (VR), is still limited. Furthermore, the integration of local cultural elements into mathematics learning is not yet optimal. This community service activity aims to improve teacher competency in designing and developing Web Augmented Reality (WebAR)-based mathematics learning media through the Techno-Ethno-Realistic Mathematics Education (TE-RME) approach. The activity was carried out through the stages of needs analysis, preparation of training materials, workshop implementation, practical mentoring, and evaluation of training results. Participants were mathematics teachers who were members of the Mathematics MGMP who were given training on basic AR/VR concepts, utilization of the WebAR platform, integration of ethnomathematics elements, and application of Realistic Mathematics Education (RME) principles in developing learning media. Evaluation was conducted using pretest and posttest instruments, participant response questionnaires, and assessment of the resulting media products. The results of the activity showed an increase in participants' understanding and skills in developing WebAR-based mathematics learning media. Participants were able to produce AR/VR media prototypes that integrated local cultural contexts and mathematical concepts contextually. Participants' responses to the training were very good, particularly regarding the ease of use of the technology, the relevance of the material, and the potential for implementation in learning. Thus, this training was effective in improving teachers' digital competencies and supporting the development of innovative, contextual, and culturally based mathematics learning.